Skill Mismatch and the Gendered Structuring of Women’s Labor Market Reintegration: A Comparative Analysis of Advanced and Developing Asian Economies - LEE, Hyeseung; Samputra, Palupi Lindiasari; Iskandar, Kurniawaty (Dinasti Publisher, 2026)
This research identifies the challenges faced by women when they want to return to work after caring for their baby, and how these challenges differ depending on the economic level of Asian countries. Founded on Gender Segmentation Theory, the research investigates how care systems and responsibilities limit employment opportunities, commonly leading women into unstable or informal employment. A systematic literature review was conducted in line with PRISMA guidelines, with searches carried out across major databases (Scopus, ScienceDirect, JSTOR and Google Scholar) in February 2026. A total of 20 relevant articles were selected from the 169 articles identified. The findings indicate that there are systemic limitations to labor reintegration. In advanced economies, women are primarily forced into non-regular employment due to continuous care responsibilities, while in developing countries, strict social norms often push them into informal or self-employment. Overall, the research suggests that current labour market regulations persist in exacerbating the gender gap. It emphasizes the urgent need for stronger re-entry pathways and inclusive policy frameworks across Asia to avoid the undervaluation of female human capital.